Mediating role of body‐related shame and guilt in the relationship between weight perceptions and lifestyle behaviours - K. M. Lucibello; C. M. Sabiston; E. K. O'Loughlin; J. L. O'Loughlin (Wiley, 2020)
Summary Introduction A substantial proportion of individuals with overweight or obesity perceive themselves as 'too heavy' relative to 'about right'. Perceiving one's weight as 'too heavy' is associated with lower levels of physical activity and higher levels of sedentary behaviour. However, the mechanisms underpinning the associations between weight perception and lifestyle behaviours have not been identified. Based on theoretical tenets and empirical evidence, the self‐conscious emotions of shame and guilt may mediate these associations. Methods Participants were young adults (n = 618, Mage = 24.0 ± .6 years) who provided data on weight, weight perception, body‐related shame and guilt, physical activity and screen time. Results Mediation analyses using the PROCESS macro indicated that shame and guilt significantly mediated the relationships between weight perception and physical activity and shame significantly mediated the relationship between weight perception and screen time. Conclusions These findings provide preliminary evidence that self‐conscious emotions may be mechanisms by which weight perception influences physical activity and sedentary behaviour in young adults. However, longitudinal investigations of this mechanism are needed.